1992
DOI: 10.1104/pp.99.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Nodule Development by Supplementation of Rhizobium leguminosarum biovar phaseoli Purine Auxotrophs with 4-Aminoimidazole-5-Carboxamide Riboside

Abstract: Purine auxotrophs of Rhizobium leguminosarum biovar phaseoli CFN42 elicit uninfected pseudonodules on bean (Phaseolus vulgaris L.). Addition of 4-aminoimidazole-5-carboxamide (AICA) riboside to the root medium during incubation of the plant with these mutants leads to enhanced nodule development, although nitrogenase activity is not detected. Nodules elicited in this manner had infection threads and anatomical features characteristic of normal nodules, such as peripheral vasculature rather than the central vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…By contrast, it has been reported that 5-aminoimidazole-4-carboxamide (AICA) riboside, which is a nonphosphorylated derivative of the purine biosynthetic intermediate AICA ribonucleotide (AICAR), promoted the symbiosis of purine mutants. Similar findings have been reported in several other cases (10,15,16,17).…”
supporting
confidence: 79%
“…By contrast, it has been reported that 5-aminoimidazole-4-carboxamide (AICA) riboside, which is a nonphosphorylated derivative of the purine biosynthetic intermediate AICA ribonucleotide (AICAR), promoted the symbiosis of purine mutants. Similar findings have been reported in several other cases (10,15,16,17).…”
supporting
confidence: 79%
“…Potentially more revealing for understanding infection are deficiencies that allow nodules or pseudonodules to form but lead to poorly developed infection threads. This phenotype has been found mainly in polysaccharide-contain extensive internal membranes but appear to lack bacteroids (21). It seems, therefore, that AICA riboside restores almost complete infection thread development but cannot overcome a second limitation that prevents the proliferation of bacteroids.…”
mentioning
confidence: 99%
“…Microscopic examination reveals that the infection threads in these nodules are distended and cease development within the root hair or the subjacent cell layer (35). Closely resembling the development of nodules elicited by mutants that do not infect at all (46), the resulting nodule structure lacks most features of a normal mature nodule and has been described as a pseudonodule (27,35). Oantigen-deficient mutants of Rhizobium leguminosarum and Bradyrhizobium japonicum also exhibit defects in infection and cause aberrant development of nodules on their respective host legumes (4,12,22,23,37,38,39,44).…”
mentioning
confidence: 99%